2022
DOI: 10.1111/basr.12271
|View full text |Cite
|
Sign up to set email alerts
|

Social services provision and stakeholder engagement in the Nigerian informal sector: A systemic concept for transformation and business sustainability

Abstract: The informal business sector has made enormous contributions to Nigeria's economic growth and development, but this sector is not given the necessary attention to transforming these businesses toward sustainability. This study explores the depth of informal business sector practices in Nigeria. It underscores the inputs of stakeholders in the transformation of businesses in the Nigerian informal sector to increase tax remittances and employment generation for job security in the Nigerian economy. Also, it unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…The study will also aid lawmakers to make amendments to legislation, regulations, and policies when Nigeria’s Nationally Determined Contributions are not reflected in domestic laws. 73 Given the significance of including Nigeria’s international climate change obligations in domestic legislation like the PIA, regulators in Nigeria would be better prepared to enforce the current laws, rules, and policies and fulfil the country’s international obligations; therefore, in view of the findings above, and in relation to achieving the intendment of the Nigeria’s PIA 2021, this study recommends as follows: The Nigeria’s PIA should be amended to include provisions which cater for the underlisted: petroleum corporations must be compelled to install suitable gas recapturing and/or re-injection facilities, similar to what is performed in developed countries. Gas flaring must also be outrightly prohibited with no exceptions.…”
Section: Discussionmentioning
confidence: 99%
“…The study will also aid lawmakers to make amendments to legislation, regulations, and policies when Nigeria’s Nationally Determined Contributions are not reflected in domestic laws. 73 Given the significance of including Nigeria’s international climate change obligations in domestic legislation like the PIA, regulators in Nigeria would be better prepared to enforce the current laws, rules, and policies and fulfil the country’s international obligations; therefore, in view of the findings above, and in relation to achieving the intendment of the Nigeria’s PIA 2021, this study recommends as follows: The Nigeria’s PIA should be amended to include provisions which cater for the underlisted: petroleum corporations must be compelled to install suitable gas recapturing and/or re-injection facilities, similar to what is performed in developed countries. Gas flaring must also be outrightly prohibited with no exceptions.…”
Section: Discussionmentioning
confidence: 99%
“…The study will also aid lawmakers to make amendments to legislation, regulations, and policies when Nigeria's Nationally Determined Contributions are not reflected in domestic laws. 73 Given the significance of including Nigeria's international climate change obligations in domestic legislation like the PIA, regulators in Nigeria would be better prepared to enforce the current laws, rules, and policies and fulfil the country's international obligations; therefore, in view of the findings above, and in relation to achieving the intendment of the Nigeria's PIA 2021, this study recommends as follows: The Nigeria's PIA should be amended to include provisions which cater for the underlisted: a. petroleum corporations must be compelled to install suitable gas recapturing and/or re-injection facilities, similar to what is performed in developed countries. Gas flaring must also be outrightly prohibited with no exceptions.…”
Section: Discussionmentioning
confidence: 99%
“…They argue that through their transformation they are positioned to make better contributions to the national economy. As a result of this, it has been observed that the Nigerian government has on several occasions provided soft loans to finance business transformation and sustainability [ 30 , 31 ].…”
Section: Literature Reviewmentioning
confidence: 99%